PENGARUH FAKTOR FUNDAMENTAL TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR KHUSUSNYA PULP & PAPER YANG TERDAFTAR DI BURSA EFEK - Rita Rita; Zahara Fatimah (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2021)
In predicting stock prices there are basic approaches namely fundamental analysis and technical analysis, this analysis determines the company’s financial performance using ratios. Some types of ratio analysis that can be used include Return On Assets (ROA), Debt to Equity Ratio (DER), Return On Equity (ROE), and Book Value per Share (BVS). This research uses explanatory research methodology. Sample of research used companies listed on the Indonesian Stock exchange particularly Pulp & Paper. Based on the result of Correlation and Regression obtained, it can be seen that all the variable ROA, ROE, DER, and BVS are affected the stock price but the significant is variable BVS